Training Needs of Poultry Farmers in Hilly Areas - R. P. Sahu; N. K. Singh (Indian Journal of Extension Education, 2014)
Temperature of brooder, time of removal of chick guard, type of brooding system, method of providing feed to the brooding chicks, duration of heating brooder, house before chicks to brood, number of brooding days and purpose of chick guard, were perceived by the poultry farmers as more important training needs in brooding practices. While the aspects like percentage of moisture to be maintained in litter, period of regular and slight hoeing of litter in a viable shed, thickness of litter material to be added every month, replacement of litter from a viable poultry unit and basic qualities of the litter material were considered as more important training needs under litter management practices. The poultry farmers perceived that dose of fowl pox vaccine, age at which vaccination against fowl pox is done, dose of mareek’s disease vaccine, age at which vaccination against mareek’s disease is done, medicine used to kill internal parasites and rate of coccidistat for mixing with feed were the more important training needs in vaccination practices. Whereas, under feeding practices, source of vitamin in feed, source of protein in feed, source of minerals in feed and source of carbohydrates in feed were considered as more important training needs. Training assumes a special recognition in view of growing sophistication in poultry farming and allied technology. In order to make a training more meaningful and effective, the training needs of the poultry farmers have to be identified before implementing any training programme. The present study was undertaken with the objective to assess the training needs of poultry farmers in Bageshwar district of Uttarakhand.